The intergenerational social mobility of children from working-class backgrounds in Germany and Britain - Betthäuser, B (2017)
Research in social stratification has shown that children from working-class backgrounds have substantially lower levels of education and tend to obtain lower labour market positions than children from higher social class backgrounds. However, we still know little about the macro- and micro-level dynamics that underlie this empirical regularity. This dissertation investigates the role of different macro-level institutions and micro-level processes in accounting for the educational and labour market inequality between individuals from working-class backgrounds and individuals from higher social class backgrounds in Germany and Britain. Moreover, we investigate the extent to which there are intra-class differences in the educational and labour market prospects of individuals from unskilled and skilled working-class backgrounds. The first paper, titled Left behind? Over-time change in the social mobility of individuals from unskilled working-class backgrounds in Germany, examines the labour market chances of people from unskilled working-class backgrounds, relative to individuals from skilled working-class and more advantaged backgrounds, and how they have changed across four cohorts born between 1940 and 1979 in Germany. Having established the over-time pattern in the inequality in labour market chances between these groups, the paper examines whether and to what extent this inequality can be attributed to crossclass differences in educational attainment. The second and third paper seek to contribute to the debate in social stratification scholarship on the effect of institutional change on the intergenerational transmission of inequality. The second paper, titled Educational inequality after state socialism: The effect of German unification revisited, draws on the natural experiment of German unification to examine, first, whether state socialism in the GDR succeeded in realising its ideological commitment to increasing the educational attainment of children from working-class backgrounds, relative to children from more advantaged backgrounds. Second, it assesses whether the restructuring of the East-German educational system and economy in the wake of German unification led to a convergence in the level of educational inequality in East Germany towards that of West Germany. To address these two research aims, we compare changes in the class gradient in educational attainment in East and West Germany across six birth cohorts, including three cohorts of individuals who completed their schooling after unification. The third paper, titled Fostering equality of opportunity? Compulsory schooling reform and social mobility in Germany, analyses the effect of one specific policy reform, the extension of compulsory schooling in Germany, which has been argued to have led to a decrease in educational inequality and an increase in social mobility. Using a difference-in-difference design, the paper exploits the variation in the timing of the reform across German states to estimate the reform effect on the educational attainment and labour market chances of individuals from different social class backgrounds. While the first three papers focus on over-time change in the educational and labour market chances of children from working-class backgrounds and the role of macro-level institutional reforms therein, the fourth paper, titled Understanding the mobility chances of children from working-class backgrounds in Britain: How important are cognitive ability and locus of control?, seeks to contribute to our understanding of the micro-level processes that account for the tendency of individuals from working-class backgrounds to obtain lower levels of educational attainment and lower labour market positions than children from higher social class backgrounds. To this end, we take a path-analytical approach to shed light on the role of two individual-level characteristics, cognitive ability and locus of control — i.e. people’s sense of control over their own lives — in mediating the effect of individuals’ parental class background on their educational attainment and social class position in Britain.